PROBLEMATIKA PELAKSANAAN PERATURAN MENTERI AGRARIA TENTANG LAHAN SAWAH YANG DILINDUNGI - Nawir, Muhammad; Sudarmanto, Kukuh; Arifin, Zaenal (PSHPM Untag Semarang, 2024)
This research aims to analyze the implementation of Minister of Agrarian Regulation No. 1589/SK-HK.02.01/XII/2021 on protected rice fields in Tegal Regency and the impact of the implementation of Minister of Agrarian Regulation No. 1589/SK-HK.02.01/XII/2021 on protected lands in Tegal Regency. The urgency of this research is so that the community can obtain legal certainty regarding the status of the land they own after the stipulation of Minister of Agrarian Regulation Number 1589, so that business actors can continue their business again. This type of research is sociological. Sociological jurisprudence is research that aims to obtain legal knowledge empirically by going directly into the object or experimenting with analysis. The results of this research show that the implementation of Minister of Agrarian Regulation No. 1589/SK-HK.02.01/XII/2021 on rice fields in Lindugi in Tegal Regency has complied with the applicable regulations from the central government, but in its implementation obstacles were encountered, namely the differences in land zone maps between the central and regional governments. Minister of Agrarian Affairs Regulation No. 1589/SK-HK.02.01/XII/2021 regarding rice fields in Lindugi is the legal umbrella for implementing control over the conversion of rice fields in Tegal Regency.